Methodology of adipose tissue type detection in mammals - I. M. Chernukha; N. V. Kupaeva; J. A. Smirnova; A. G. Akhremko; V. A. Pchelkina; E. A. Kotenkova (Теория и практика переработки мяса, 2023)
Nowadays, an interest in studying the composition, properties and functions of adipose tissue (AT) is growing among researchers, which is conditioned by its important role in the normal functioning of the body. Due to different types of adipose tissue (AT) in mammals (white, beige, brown and pink) and different physiological tasks performed by each type of AT, rapid, correct and effective detection of an AT type is highly topical. Methods used today are labor consuming and in the case of NMR and CT expensive, which limits possibilities of scientists. In this connection, the aim of this research was to develop a methodological approach allowing rapid and effective detection of an adipose tissue type. A methodology was formed based on the concept, formalized requirements for the method, step-wise structure of investigations and interpretation of results. The concept is based on differences in the structure of the adipose cell (adipocyte) of different AT types. The method is based on extraction of heme containing proteins. To this end, solvents and parameters of extraction that facilitate their better extraction have been chosen. An AT type has been determined by the total content of iron contained in the cytochrome fragment. Our own modification was selected. This modification includes preliminary mincing of a sample with the ice-cold TES buffer (pH 8.5) in a ratio of 1:5 (g: mL), homogenization at 9,000 rpm for 2 min with the following centrifugation at 10,000 g and 4 °C for 15 min. Effectiveness of the proposed method was confirmed by the histological and electrophoretic analyses. Therefore, the new methodology of identification and differentiation of adipocytes was proposed for rapid and effective detection of an adipose tissue type.